A Three (or More) Factor Model of Growth with Induced Innovation - Brewer, A. A. (Review of Economic Studies, 1975)
Journal Article A Three (or More) Factor Model of Growth with Induced Innovation Get access A. A. Brewer A. A. Brewer University of Bristol Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 2, April 1975, Pages 285–292, https://doi.org/10.2307/2296536 Published: 01 April 1975